A necessary condition for the regularity of a boundary point for degenerating parabolic equations with measurable coefficients - Skrypnik, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We prove a necessary condition for the regularity of a point on a cylindrical boundary for solutions of second-order quasilinear parabolic equations of divergent form whose coefficients have a superlinear growth relative to derivatives with respect to space variables. This condition coincides with the sufficient condition proved earlier by the author. Thus, we establish a criterion for the regularity of a boundary point similar to the well-known Wiener criterion for the Laplace equation.